Band structure study of graphene and transition metal dichalcogenides heterostructures - Ahmed, Saif; Ahmed, Nafisa Nowshin; Nur, Juhayer An (BRAC University, 2017)
This thesis report is submitted in partial fulfilment of the requirements for the degree of Bachelor of Science in Electrical and Electronic Engineering, 2017.